Toxoplasma Effector GRA15-Dependent Suppression of IFN-γ-Induced Antiparasitic Response in Human Neurons - Bando, Hironori; Lee, Youngae; Sakaguchi, Naoya; Pradipta, Ariel; Sakamoto, Ryoma; Tanaka, Shun; Ma, Ji Su; Sasai, Miwa; Yamamoto, Masahiro (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii is an important human and animal pathogen that causes life-threatening toxoplasmosis. The host immune system produces interferon-γ (IFN-γ) to inhibit T. gondii proliferation. IFN-γ-inducible indole-2,3-dioxygenase 1 (IDO1), which mediates tryptophan degradation, has a major role in anti-T. gondii immune responses in various human cells. In response to the host’s immune system, T. gondii secretes many virulence molecules into the host cells to suppress IFN-γ-dependent antiparasitic immune responses. The GRA15-induced proparasitic mechanism for suppressing IDO1-dependent immune responses has previously been tested only in human hepatocyte and monocyte cocultures. Thus, whether human cells other than hepatocytes contain this virulence mechanism remains unclear. Here, we show that the GRA15-dependent virulence mechanism for suppressing the IDO1-dependent anti-T. gondii response operates in human neuronal cell lines and primary human neurons. Analysis of various human cell lines revealed that IL-1β-induced iNOS-dependent reduction of IDO1 mRNA expression occurred in brain cell lines (A172; glioblastoma, IMR-32; neuroblastoma, and T98G; glioblastoma) and liver cell lines (Huh7 and HepG2), but not in other cell lines. Moreover, coculturing type II T. gondii-infected THP-1 human monocytes with the brain cell lines inhibited the IDO1-mediated anti-T. gondii response in a GRA15-dependent manner. These data suggest that a GRA15-dependent virulence mechanism antagonizes the IDO1-dependent host immune response in human brain cells.